The Term Dekengane Pusat and its Relevance to the Hadith of Al-Bukhari No. 6502: A Study of Fazlur Rahman’s Hadith Hermeneutics - Mohammad Fajar Alchusyairi; Ibnu Hajar Ansori (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
This research aims to reinforce this explanation and ensure that public understanding remains aligned with the principles of Islam. The term dekengane pusat was first introduced by Gus Iqdam, a young preacher from Blitar, who emphasised that those who perform Sunnah prayers and draw closer to Allah will be protected by Him. This concept aligns with the hadith narrated by al-Bukhari no. 6502, which discusses the saints of Allah (awliya’). The hadith highlights the spiritual connection between believers and their Creator through acts of worship. The study employs a literature-based approach, examining primary references such as al-kutub al-tis’ah (the nine canonical hadith collections), as well as secondary sources, including books and academic articles. Using Fazlur Rahman's double movement hermeneutical method, this research provides an in-depth analysis of the hadith from al-Bukhari no. 6502. The methodology consists of two stages: first, understanding the hadith in its original context, and second, applying the general principles derived from this analysis to contemporary contexts to ensure the continued relevance of the hadith. The findings illustrate that this hadith, classified as hadith qudsi, is based on Allah’s direct communication to the Prophet Muhammad (SAW), emphasising the relationship between Allah’s beloved individuals and His guarantee oh protection. Contextually, the viral term dikencani pusat serves as a reminder for a society that closeness to Allah is the core of worship, regardless of one’s social status.